THE EFFECTIVENESS OF A BOARD GAME FOR TEACHING SPEAKING TO THE SEVENTH GRADERS OF MTs. NU TERATE GRESIK (RETAIN, 2013)
Speaking is one of the four skills that should be mastered by students. Whereas, most of the speaking class activity is lack of media. This research provided a board game as media for teaching speaking. Kipple (1984) used it for communicative fluency in classroom speaking activity. This research is conducted to find the significant difference in speaking ability of expressing likes and dislikes between the students who were taught by using a board game and those who were taught without using a board game. It is also purposed to find out the students’ responses toward the effectiveness of a board game in teaching speaking. Some of reasons why a board game is chosen are the advantage of a board game and the ease of a board game when it is conducted in speaking class activities. A board game enables to encourage students’ speaking confidence, develop students’ speaking fluency, and encourage the development of short conversation. In application, a board game can be arranged easily, based on the students’ material. This research is an experimental research that takes population and sample in MTs. NU Terate Gresik. The population of this study was the seventh graders of MTs. NU Terate Gresik while the sample of this study, which taken by using cluster random sampling, are VII C (as experimental group) which got treatment and VII E (as control group) which did not get the treatment. Each group consists of 38 students. There are two instruments to collect the data; they are test and questionnaire. T-test formula is used to analyze the test instrumen, whether, the questionnaire instrument, percentage formula is used. The result is the critical value for rejecting the null hypothesis at p ≤ .001 df 74 is 2.38 and the result of t-test is 4.56. It means that t-test is larger than critical value (4.56>2.38). It can be said that null hypothesis was rejected. Meanwhile, the result of the questionnaire shows most students responded enjoyed, were motivated and helped in speaking English by using a board game. Key Words: Speaking, Teaching Speaking, Likes and Dislikes Expression, and a Board Game.